The Social Capital Ability to Communal Cattle Survive in Rural of Special Region of Yogyakarta, Indonesia - Fajar Julian Santosa; Retno Setyowati; Agung Wibowo (Universitas Djuanda, 2023)
Globalization has led to a capital transformation that alters culture, values, and human attitudes, making people more individualistic. Social capital acts as a social glue by fostering trust, social norms, cooperation, and a sense of community. This paper will discuss how social capital can be a driving factor for the survival of communal cattle. We conducted this research in Kulwaru Village, Special Region of Yogyakarta. This study used a qualitative approach with data collection through observation, Focus Group Discussion (FGD), in-depth interviews with key informants, and study of program-related documents. The data obtained were then analyzed using an interactive model. The results of the study show that the existence of social capital in the communal cattle in Kulwaru Village has a vital role in shaping social values in society, such as trust, norms, social relations, and cooperation which provides strong bonds in communities both in bonding, bridging, and linking. This factor has made the communal cattle survive for the last twelve years. The findings of this research will contribute to understanding and harnessing the social capital of rural communities; it is possible to support the continuation of this traditional practice and contribute to the economic and cultural well-being of the communities involved.